Genetic Diversity of Four Pig Breeds in Thailand Based on Microsatellite Analysis - Wanee Chaiwatanasin; Somchai Chantsavang; Sompoch Tabchareon (Agriculture and Natural Resources, 2002)
Fourteen microsatellite loci were analyzed in 79 random individuals to characterize the genetic variability of Thai native pig breed (TN), Large White (LW), Spotted Large White (SLW), and Pietrain (PT). Mean numbers of allele per locus, mean numbers of shared allele per locus and average gene diversity per locus were 8.86, 1.86 and 0.7875, respectively. Polymorphism information content (PIC), observed and expected heterozygosity of TN (0.7555, 0.5335 and 0.7925) were higher than the values in LW (0.5468, 0.5571 and 0.6707), SLW (0.5300, 0.5800 and 0.6492) and PT (0.4874, 0.4545 and 0.5986). Base on Nei’standard genetic distance and phylogenetic tree constructed using Nei’ standard genetic distance matrix, there were a great genetic differentiation between TN and the other three breeds.